Mass balance, metabolism, and pharmacokinetics of [14C]amdizalisib, a clinical-stage novel oral selective PI3Kδ inhibitor for the treatment of non-hodgkin’s lymphoma, in healthy Chinese volunteers - Zhao, Chun-Yang; Zhang, Li-Jun; Sun, Chan; Yu, Cheng-Yin; Wang, Jian; Sai, Yang; Su, Wei-Guo; Chen, Qian; Wang, Wei; Jia, Jing-Ying; Liu, Gang-Yi; Liu, Yan-Mei (Frontiers in Pharmacology, 2024)
Amdizalisib (HMPL-689) is an ATP-competitive PI3Kδ inhibitor under study for treating Hodgkin's lymphoma. This trial assessed the metabolism, excretion, pharmacokinetics, and safety of amdizalisib in six healthy Chinese male volunteers who received a single oral dose of 30 mg/100 µCi [ 14 C]amdizalisib suspension.Amdizalisib is rapidly absorbed in human with the median Tmax of 2.5 hours. The Cmax of amdizalisib was 244±48.9 ng/mL and the AUC0-t was 1870±474 h•ng/mL after a single oral dose of 30 mg amdizalisib suspension. The blood-to-plasma total radioactivity ratio was less than 1 and ranged from 0.561 to 0.645, indicating that there was no significant affinity of [ 14 C]amdizalisib and its metabolites to blood cells and the radioactive material is mainly distributed in plasma. The drug was mainly excreted from feces and urine with the radioactivity of 62.08%±3.00% recovered in the feces and 37.15%±2.84% in urine, among of which over 94% of the drug excreted within 96 hours. The predominant radioactive component in plasma was the parent drug (accounting for 51.45% of total plasma radioactivity). Additionally, 11 metabolites were identified in plasma, urine, and feces, and the metabolic pathways include oxidation on the benzene or pyrimidine rings and conjugation with cysteine or glucuronic acid. The major metabolites in plasma were the di-oxidized and hydrogenated product (M424) and the mono-oxidized product (M406-2), accounting for 16.67% and 20.91% of total plasma radioactivity, respectively. Both of these two metabolites are also the major radioactive components in urine and feces, among of which M424 accounted for 21.01% and 14.26%, M406-2 accounted for 8.08% and 11.30%, of the administered dose in urine and feces, respectively. In addition, the di-oxidized and methylated product (M436) was also one of the major metabolites in feces accounting for 17.7% of the administered dose. Few of the parent drug was found in urine and feces, suggesting that amdizalisib is primarily metabolized in the liver. The study reported no serious adverse events or drug-related deaths, with diarrhea as the most common adverse event. These results support further development of amdizalisib, providing a strong foundation for its clinical application in cancer treatment.